2019
DOI: 10.1098/rspb.2019.1527
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamics reveals extinction–recolonization dynamics underpin apparently endemic vampire bat rabies in Costa Rica

Abstract: Variation in disease incidence in wildlife is often assumed to reflect environmental or demographic changes acting on an endemic pathogen. However, apparent endemicity might instead arise from spatial processes that are challenging to identify from traditional data sources including time series and field studies. Here, we analysed longitudinal sequence data collected from rabies virus outbreaks over 14 years in Costa Rica, a Central American country that has recorded continuous vampire bat-transmitted rabies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 49 publications
9
33
0
Order By: Relevance
“…More broadly, however, our results suggest that the degree of connectivity found here likely enables virus persistence through inter-site contacts but is not sufficient to synchronize infection dynamics across sites (Blackwood et al, 2013). In further support of this idea, the inverse relationship in seroprevalence between our Belize sites (<10 km) is consistent with prior rates of RABV dispersal in vampire bats of 9-17 km per year (Benavides et al, 2016;Streicker et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…More broadly, however, our results suggest that the degree of connectivity found here likely enables virus persistence through inter-site contacts but is not sufficient to synchronize infection dynamics across sites (Blackwood et al, 2013). In further support of this idea, the inverse relationship in seroprevalence between our Belize sites (<10 km) is consistent with prior rates of RABV dispersal in vampire bats of 9-17 km per year (Benavides et al, 2016;Streicker et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Future phylogenetic analyses of RABV isolates from across Belize as well as nearby countries could help differentiate hypotheses of a persistent transmission cycle in Belize against the potential role of viral invasions and spatial spread (Andrés Velasco-Villa et al, 2006;Biek et al, 2007;Streicker et al, 2019). Although our serological data are consistent with endemic maintenance of RABV in local vampire bat populations, livestock rabies outbreaks are known to show epidemic dynamics, including in Belize, where outbreaks were not reported in livestock in 2014 and 2015 (World Organization for Animal Health, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although undersampling of active infections cannot be discarded, one likely explanation for this apparent discrepancy is that the virus undergoes localized epizootics, during which prevalence is substantially elevated, followed by local extinctions. Indeed, such invasion-extinction dynamics are readily observed in the complex spatiotemporal patterns of spillover to livestock, including epizootic waves, where DRRV spreads across the landscape via transmission between neighboring bat colonies at a relatively constant speed [10] and metapopulation persistence, where asynchronous presence of the virus in bat colonies prevents extinction at a larger spatial scale, and localized lineage replacements [33,40,41]. Extended incubation periods can occur but are a less plausible explanation for localized disappearances of DRRV strains over multiple years suggested by passive surveillance of livestock [40].…”
Section: Current Knowledgementioning
confidence: 99%
“…Bat population was monitored for rabies by fluorescent antibody testing and simplified fluorescent inhibition microtesting by Almeida et al [14], who indicated an increase in rabies virus circulation among bats and risk of a rabies outbreak. Streicker et al [15] highlighted the importance of international viral dispersal for shaping the burden of rabies in Costa Rica and suggested a Central American corridor of rabies virus invasions between continents. Although researchers have carried out a lot of studies on bat rabies from different aspects, there are relatively few studies on relevant mathematical analysis from the perspective of the dynamic model.…”
Section: Introductionmentioning
confidence: 99%